Analisis Performa Layanan Karyawan BMT NU Cabang Kota Kraksaan Probolinggo Terhadap Loyalitas Nasabah - Saifuddin, Saifuddin; Moh. Idil Ghufron; Tarwiyadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
BMT NU Branch of the city of Kraksaan Probolinggo is a Syrian financial institution that is one of the containers to empower the poor. There is one role that can support success in the banking sector, and that is to offer quality service by improving the service performance of employees who are good, friendly, and polite, which can increase customer loyalty. This study aims to describe the results of the analysis based on the focus of the researchers, namely (1) the role of BMT NU Branch Kraksaan in meeting the needs of the community and (2) the service performance of BMT NU Branch Kraksaan City in improving customer loyalty. This research is field research with a qualitative approach, data collection with the results of interviews, documentation, data analysis techniques starting with data verification and using triangulation of data sources, as well as a series of data analyses. The results of this research are the first: with the existence of the BMT NU branch in the city of Kraksaan, the economy of the people in Kraksaan district has undergone a fairly good change. And with the presence of BMT Nu Branch, the people feel like they have a vision of their future because they are beginning to learn to save for it. The second service performance is a sticker so that customers more trust BMT NU Branch of Kraksaan as well as the opposite, efforts in shaping customer loyalty (1) create performance and quality of service that is trustworthy and professional; (2) create transparency or openness in the development of product marketing..